Magnetic investigation of an unusual dissymmetric binuclear manganese carboxylate complex [Articol] - Novițchi, Ghenadie; Costes, Jean-Pierre; Popovschi, Lilia; Șova, Sergiu; Gulea, Aurelian (My University, 2006)
The magnetic susceptibility (χT) of an unusual dissymmetric binuclear manganese corboxylate complex has been measured from 2 to 300K. The magnetic data which have been fitted with help of the Heisenberg Dirac Van Vleck HDVV spin-exchange Hamiltonian H = −J S1S2ur ur, indicate that an antiferromagnetic interaction equal to J = -0.90(1) cm-1 is present. A correlation between J values and Mn-H2 O-Mn angles has been tempted.
Keywords: manganese(II) carboxylates; magnetic properties